Forever Cousins - Goodluck, Laurel; Nelson, Jonathan (Illustrator) (Watertown, MA : Charlesbridge, 2022)
Amanda and Kara are cousins and best friends in an intertribal Native American family; but Kara's family leaves the city and moves back to the Rez, making both girls sad; but the summer reunion reminds them that they will always be cousins.
Junior Library Guild
Ages 5-6.
Grades K-1.
AD610
A Junior Library Guild selection
Keywords: Best friends -- Juvenile fiction; Cousins -- Juvenile fiction; Indians of North America -- Juvenile fiction; Moving, Household -- Juvenile fiction; Best friends -- Fiction; Cousins -- Fiction; Friendship -- Fiction; Indian reservations -- Fiction; Indians of North America -- Fiction; Moving, Household -- Fiction; Picture books; Cousins -- Fiction; Friendship -- Fiction; Moving -- Fiction; Native Americans -- Fiction; Native Americans -- Fiction. -- Reservations; Picture books for children; Picture books